Industrial Training Report: Perpustakaan UTM Kuala Lumpur / Serena Md Nor Manokaran - Md Nor Manokaran, Serena (Faculty of Information Management, 2015)
As part of the Bachelor of Information Management course requirement, all seventh semester students have to complete five months of compulsory practical attachment in either government or private sector organizations. It provides an opportunity for the students to experience real working environment first hand while at the same time benefit us in terms of our personal and professional development. Undergo the industrial training in Universiti Teknologi Malaysia (UTM) Kuala Lumpur (KL) Library was the most interesting, productive and instructive experience. Furthermore, feedbacks from the library staffs help me in improving the character and professional skills of the graduate to acquaint with the structure of an organization and its management system. This industrial training also gives the opportunity to me about the understanding the organization's work ethics in terms of interpersonal interaction, discipline, rules and regulations of performing assigned tasks. It also improves self-confidence through acquired hard skill and soft skill.